Supportive care in the acute phase of Stevens–Johnson syndrome and toxic epidermal necrolysis: an international, multidisciplinary Delphi‐based consensus. (27th April 2021) - Brüggen, M.‐C.; Le, S.T.; Walsh, S.; Toussi, A.; de Prost, N.; Ranki, A.; Didona, B.; Colin, A.; Horváth, B.; Brezinova, E.; Milpied, B.; Moss, C.; et al.
Summary: Background: Supportive care is the cornerstone of management of adult and paediatric Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). However, consensus on the modalities of supportive care is lacking. Objectives: Our aim in this international multicentric Delphi exercise was to establish a multidisciplinary expert consensus to standardize recommendations regarding supportive care in the acute phase of SJS/TEN. Methods: Participants were sent a survey via the online tool SurveyMonkey, consisting of 103 statements organized into 11 topics: multidisciplinary team composition, suspect drug management, infection prevention, fluid resuscitation and prevention of hypothermia, nutritional support, pain and psychological distress management, management of acute respiratory failure, local skincare, ophthalmological management, management of other mucosa, and additional measures. Participants evaluated the level of appropriateness of each statement on a scale of 1 (extremely inappropriate) to 9 (extremely appropriate). The results were analysed according to the RAND/UCLA Appropriateness Method. Results: Forty‐five participants from 13 countries (on three continents) participated. After the first round, a consensus was obtained for 82.5% of the 103 initially proposed statements. After the second round, a final consensus was obtained for 102 statements. Conclusions: We have reached an international Delphi‐based consensus on best supportive care practice for SJS/TEN. Our expert consensus should help guide physicians in treating patients with SJS/TEN and thereby improve short‐term prognosis and the risk of sequelae. Abstract : What is already known about this topic? Supportive care is the cornerstone of management of Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) in the acute phase. There is no consensus or guideline on the best supportive care. What does this study add? An international, multidisciplinary consensus on best supportive care practices for patients with SJS/TEN in the acute phase, along with practical guidance. Linked Comment:  C.-B. Chen and W.-H. Chung. Br J Dermatol 2021; 185:484–486 .